في المدرسة الثنوية الحكومية ۲ ديلي سردانغ (DBL) تطبيق تعليم اللغة العربية من خلال التعليم القائم على التمايز - Syaputri, Nahwa; Zulheddi, Zulheddi (Shaut al Arabiyyah, 2025)
Differentiated based learning is an effective learning process that considers the differences of each student in increasing their potential according to their readiness, interest and learning profile. The purpose of this research is to find out how the implementation of learning in Arabic language teaching at Madrasah Aliyah Negeri 2 Deli Serdang through the Differentiated Based Learning (DBL) approach. The method used in this research is descriptive qualitative research which involves observation of Arabic language teaching at Madrasah aliyah Negeri 2 Deli Serdang, and responses from teachers and students to the approach. The findings show that Arabic language learning is an important aspect of the educational curriculum in many countries, especially for educational institutions that have an Islamic religious base. In the midst of increasingly advanced educational developments, innovative learning approaches are the main focus for educators to improve the effectiveness and efficiency of Arabic language learning. Where teachers are able to adapt learning to students' individual learning styles, needs and interests by improving students' understanding of Arabic by providing variety in teaching and meeting individual learning needs. This research makes an important contribution to the development of Arabic language teaching approaches at the secondary level.